Direct molecular detection of a broad range of bacterial and viral organisms and Streptococcus pneumoniae vaccine serotypes in children with otitis media with effusion - Slinger, Robert; Duval, Melanie; Langill, Jonathan; Bromwich, Matthew; MacCormick, Johnna; Chan, Francis; Vaccani, Jean-Philippe (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Otitis media with effusion (OME) causes significant morbidity in children, but the causes of OME and methods for prevention are unclear. To look for potential infectious etiologies, we performed a pilot study using multiple-target real-time polymerase chain reaction (qPCR) for 27 infectious agents, including nine bacterial organisms and 18 respiratory viruses in middle ear fluids (MEFs) from children with OME. QPCR was also performed for the 13 Streptococcus pneumoniae serotypes contained in the current vaccine. Results Forty-eight MEF samples were obtained and qPCR detected bacterial nucleic acid (NA) in 39/48 (81 %) and viral NA in 7/48 (15 %). Alloiococcus otitidis and S. pneumoniae were both detected in 15/48 (31 %) MEFs, followed by M. catarrhalis in 14/48 (29 %), H. influenzae in 5/48 (10 %) and M. pneumoniae in 4/48 (8 %). Rhinoviruses were most common virus type detected, found in 4/48 (8 %) MEFs. Serotypes included in the current 13-serotype vaccine were detected in only 3/15 (20 %) S. pneumoniae qPCR-positive MEFs. Conclusions Bacteria may play an important role in OME, since over 80 % of MEFs contained bacterial NA. Further research into the role of A. otitidis in OME will be helpful. Serotypes of S. pneumoniae not included in the current 13-serotype vaccine may be involved in OME. Larger studies of OME S. pneumoniae serotypes are needed to help determine which additional serotypes should be included in future vaccine formulations in order to try to prevent OME.